2015
DOI: 10.1080/09602011.2015.1047383
|View full text |Cite
|
Sign up to set email alerts
|

Language specificity of lexical-phonological therapy in bilingual aphasia: A clinical and electrophysiological study

Abstract: Based on findings for overlapping representations of bilingual people's first (L1) and second (L2) languages, unilingual therapies of bilingual aphasia have been proposed to benefit the untrained language. However, the generalisation patterns of intra-and cross-language and phonological therapy and their neural bases remain unclear. We tested whether the effects of an intensive lexical-phonological training (LPT) in L2 transferred to L1 word production in a Persian-French bilingual stroke patient with Broca's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
0
12
0
1
Order By: Relevance
“…A related issue is the possible effect of the “linguistic distance” between each of the L1-L2 pairs studied here on the engagement of the language control system, a topic that has to date been scarcely studied. A recent clinical observation might support the fact that the distance between languages may influence language control (Radman, Spierer, Laganaro, Annoni & Colombo, 2016); however, these data have been obtained with very distant language pairs (Persian–French) and not with nearer European languages. Moreover, it is of interest that despite the absence of differences between the groups at the behavioural level (performance and reaction time), the functional analysis was still able to show that activation patterns were influenced by the difference in proficiency between groups, and by their ability to retrieve lexical information and manage the use of their two languages.…”
Section: Discussionmentioning
confidence: 93%
“…A related issue is the possible effect of the “linguistic distance” between each of the L1-L2 pairs studied here on the engagement of the language control system, a topic that has to date been scarcely studied. A recent clinical observation might support the fact that the distance between languages may influence language control (Radman, Spierer, Laganaro, Annoni & Colombo, 2016); however, these data have been obtained with very distant language pairs (Persian–French) and not with nearer European languages. Moreover, it is of interest that despite the absence of differences between the groups at the behavioural level (performance and reaction time), the functional analysis was still able to show that activation patterns were influenced by the difference in proficiency between groups, and by their ability to retrieve lexical information and manage the use of their two languages.…”
Section: Discussionmentioning
confidence: 93%
“…Laganaro et al 45 reported that ERPs in four patients with aphasia were normalised for processes that were unimpaired following aphasia therapy, while Pulvermuller et al 46 showed increased negativity around 250 to 300ms for words post-treatment, however, no change was observed for pseudowords. Radman et al 47 showed that lexical-phonological therapy in a participant with chronic bilingual aphasia modified EEG responses to treated but not untreated words consistent with modulation of brain networks involved in phoneticphonological processing. While these studies did not examine whether EEG predicted aphasia treatment response they do support the current finding that therapy success and potential for recovery involves engagement of normal left-hemisphere language networks.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, bilingual rehabilitation, the cross language transfer (CLT) of treatment benefits from one language to the other(s) is a notable topic. It is not yet clear which factors influence the success of CLT in bilingual aphasics: premorbid language proficiency, degree and type of language impairments or various forms of therapy (Miertsch et al, 2009; Faroqi-Shah et al, 2010; Kiran and Iakupova, 2011; Kiran et al, 2013; Ansaldo and Saidi, 2014; Radman et al, 2016). Moreover, if the transfer does not take place, the selective recovery of one language could be seen as partial evidence of a different neural representation of the two languages.…”
Section: Studies On L2 Embodiment Serving Clinical Purposesmentioning
confidence: 99%